Creativity and urban cultural identity: Best practices in contemporary cities. - Kolotouchkina, Olga (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
This research paper is a reflection on the role of innovation and creativity in the urban landscape. Based on the analysis of the prominence of cities in the context of globalisation and the essential role of culture for urban regeneration and competitive advantage, the paper illustrates a series of innovative urban cultural practices implemented in different cities around the world. The focus on iconic architecture, the creative transformation of urban spaces as well as the hosting of mega-events reaffirm the urban cultural identity on account of new urban narratives, innovative dynamics of cultural consumption and entertainment, creative talent attraction and boost to the creative industries. In addition, those innovative practices become the catalyst for citizen engagement and activism.